P‐138: A New Active‐Matrix‐Like Driving Technology of Floating Metal Ball Actuator Display without Transistors. Issue 1 (2nd June 2017) - Jo, Jae-Hee; Lee, Dong-gun; Kim, Min-Koo; Lee, Seung-Woo
Abstract : In this paper, we propose a novel driving technique that can be used for active‐matrix operation without using transistors. A new display using floating metal ball actuators can operate in two types of display modes such as reflective and transmissive modes (or emissive). We propose a new driving scheme without any oscillation and delay. We confirm through experiments that transistor‐free operation is possible.